Biochemical Characterization of a Carrageenase, Car1383, Derived From Associated Bacteria of Antarctic Macroalgae - Li, Jiang; Gu, Xiaoqian; Zhang, Qian; Fu, Liping; Tan, Jiaojiao; Zhao, Luying (Frontiers in Microbiology, 2022)
A carrageenase gene, car1383, was obtained from the metagenome of Antarctic macroalgae-associated bacteria. The amino acid sequence of its product showed up to 33% similarity with other carrageenases, and contained a GH16-family motif. When tThe recombinant Car1383protein was heterologously expressed in Eschericia coli, its optimal temperature and exhibited maximal activity atpH were 50 °C and pH 6.0, respectively. with a Km of 6.51 mg/ml and a Vmax of 55.77 U/mg. Its activity was enhanced by some cations (Na+, K+, and especially Fe 2+), which more than doubled its initial activity), but inhibited or inactivated by others (Sr2+, Ca2+, Ni2+, Ba2+, Mn2+, Cu2+, Fe3+, Mg2+). The Km and Vmax values for Car1383 were 6.51 mg/ml and 55.77 U/mg, respectively. Car1383 degraded carrageenan into neocarrabiose and neocarratetraose. Site-directed mutagenesis indicated that two putative active sites, E190 and E195, conserved sites, W183 and G255, play important roles in Car1383 activity. Moreover, conserved sites, W183 and G255, were substituted with the alkaline amino acid Lys, which activity were almost two-fold higher than that of wild type. This study provides a new candidate for the industrial preparation of bioactive algal oligosaccharides.